Impacts of multilayer hybrid coating on psf hollow fiber membrane for enhanced gas separation - Roslan, R.A. (MDPI AG, 2020)
One of the most critical issues encountered by polymeric membranes for the gas separation process is the trade-off effect between gas permeability and selectivity. The aim of this work is to develop a simple yet effective coating technique to modify the surface properties of commonly used polysulfone (PSF) hollow fiber membranes to address the trade-off effect for CO2 /CH4 and O2 /N2 separation. In this study, multilayer coated PSF hollow fibers were fabricated by incorporating a graphene oxide (GO) nanosheet into the selective coating layer made of polyether block amide (Pebax). In order to prevent the penetration of Pebax coating solution into the membrane substrate, a gutter layer of polydimethylsiloxane (PDMS) was formed between the substrate and Pebax layer. The impacts of GO loadings (0.0â1.0 wt) on the Pebax layer properties and the membrane performances were then investigated. XPS data clearly showed the existence of GO in the membrane selective layer, and the higher the amount of GO incorporated the greater the sp2 hybridization state of carbon detected. In terms of coating layer morphology, increasing the GO amount only affected the membrane surface roughness without altering the entire coating layer thickness. Our findings indicated that the addition of 0.8 wt GO into the Pebax coating layer could produce the best performing multilayer coated membrane, showing 56.1 and 20.9 enhancements in the CO2 /CH4 and O2 /N2 gas pair selectivities, respectively, in comparison to the membrane without GO incorporation. The improvement is due to the increased tortuous path in the selective layer, which created a higher resistance to the larger gas molecules (CH4 and N2 ) compared to the smaller gas molecules (CO2 and O2 ). The best performing membrane also demonstrated a lower degree of plasticization and a very stable performance over the entire 50-h operation, recording CO2 /CH4 and O2 /N2 gas pair selectivities of 52.57 (CO2 permeance: 28.08 GPU) and 8.05 (O2 permeance: 5.32 GPU), respectively. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.